2021
DOI: 10.3390/molecules26041110
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Cytotoxic Activity of the Fractionated Trunk Bark Essential Oil from Tetraclinis articulata (Vahl) Mast. Growing in Tunisia

Abstract: The aim of the present research was to determine the chemical composition and the cytotoxic effects of Tetraclinis articulata trunk bark essential oil (HEE) obtained by steam distillation and five fractions obtained by normal phase silica chromatographic separation. Chemical analysis allowed the identification of 54 known compounds. Relatively high amounts of oxygenated sesquiterpenes (44.4–70.2%) were detected, mainly consisting of caryophyllene oxide (13.1–26.6%), carotol (9.2–21.2%),14-hydroxy-9-epi-(E)-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To overcome multidrug resistance in MDA-MB-231 breast cancer cells and investigate whether T. articulata essential oil possesses substantial in vitro cytotoxic properties ( Table 5 ). Jlizi et al (2021) tested the in vitro cytotoxic activity of T. articulata trunk bark essential oil against MDA-MB-231 breast cancer and SW620 colon cancer using the cell viability assay (MTT). They reported that the EO exhibited moderate dose-dependent cytotoxic potency against both cell lines.…”
Section: Biological Activities Of T Articulatamentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome multidrug resistance in MDA-MB-231 breast cancer cells and investigate whether T. articulata essential oil possesses substantial in vitro cytotoxic properties ( Table 5 ). Jlizi et al (2021) tested the in vitro cytotoxic activity of T. articulata trunk bark essential oil against MDA-MB-231 breast cancer and SW620 colon cancer using the cell viability assay (MTT). They reported that the EO exhibited moderate dose-dependent cytotoxic potency against both cell lines.…”
Section: Biological Activities Of T Articulatamentioning
confidence: 99%
“…a cytotoxic effect against both cell lines MDA-MB-23, SW620, with IC50 values of 83.0 and 25.7 μg/ml, respectivelyJlizi et al (2021) …”
mentioning
confidence: 99%
“…), monoterpenes (e.g., limonene and carveol), and sesquiterpenes (e.g., β-caryophyllene and humulene) may participate in the cytotoxicity of the extract from the leaves of Tetraclinis articulata (Vahl) Mast. [28][29][30][31][32][33]. In summary, because patients with advanced cancers need selective anticancer drugs, we have searched for potential sources of selective anticancer drugs in a variety of plants.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, essential oils are complex natural combination of volatile secondary metabolites, small molecular weight and lipophilic compounds [8] . They are known to exhibit various biological properties such as antimicrobial, [9] cytotoxic, [10] antioxidant, [11] anti‐inflammatory [12] and insecticidal [13] . Therefore, these volatile compounds could be a promising eco‐friendly alternative for controlling stored product insects [14] .…”
Section: Introductionmentioning
confidence: 99%